2013
DOI: 10.1155/2013/147589
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Fast Food Consumption among Iranian High School Students Based on Planned Behavior Theory

Abstract: Objective. This study was conducted to identify some factors (beliefs and norms) which are related to fast food consumption among high school students in Isfahan, Iran. We used the framework of the theory planned behavior (TPB) to predict this behavior. Subjects & Methods. Cross-sectional data were available from high school students (n = 521) who were recruited by cluster randomized sampling. All of the students completed a questionnaire assessing variables of standard TPB model including attitude, subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
5
31
2
1
Order By: Relevance
“…Sugary snack and drink consumption (Åstrøm, 2004;Åstrøm & Okullo, 2004; and sugary beverage/soft drink intake Tak et al, 2011) accounted for nine publications. Making healthy breakfast choices was an outcome in four studies Conner et al, 2011;Hewitt & Stephens, 2007) and two trials assessed fast food consumption Sharifirad et al, 2013). Three studies measured low calorie versus high calorie snack consumption or snacking less de Bruijn et al, 2005) and four evaluated fruit or vegetable intake Lien et al, 2002;.…”
Section: Nutrition Behaviors Measuredmentioning
confidence: 99%
See 4 more Smart Citations
“…Sugary snack and drink consumption (Åstrøm, 2004;Åstrøm & Okullo, 2004; and sugary beverage/soft drink intake Tak et al, 2011) accounted for nine publications. Making healthy breakfast choices was an outcome in four studies Conner et al, 2011;Hewitt & Stephens, 2007) and two trials assessed fast food consumption Sharifirad et al, 2013). Three studies measured low calorie versus high calorie snack consumption or snacking less de Bruijn et al, 2005) and four evaluated fruit or vegetable intake Lien et al, 2002;.…”
Section: Nutrition Behaviors Measuredmentioning
confidence: 99%
“…The remaining studies reported using a food frequency questionnaire (FFQ) de Bruijn et al, 2005;de Bruijn et al, 2007;Lien et al, 2002;Tak et al, 2011;. In 13 studies it was unclear or not specified which type of which dietary evaluation tool was administered; (Åstrøm, 2004;Åstrøm & Okullo, 2004;Bazillier et al, 2011;Fila & Smith, 2006;Hewitt & Stephens, 2007;Mullan et al, 2013;Seo et al, 2011;Sharifirad et al, 2013) however, it can be inferred that a food screener or FFQ was used in six of these (Hewitt & Stephens, 2007;Mullan et al, 2013;Sharifirad et al, 2013). Studies evaluating the intention of a specified nutrition behavior (e.g.…”
Section: Types Of Nutrition Measures Usedmentioning
confidence: 99%
See 3 more Smart Citations